2016
DOI: 10.1159/000449262
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hyperautofluorescent Choroidal Vessels Using Fundus Camera Type Short-Wavelength Autofluorescence

Abstract: Purpose: To clarify differences between eyes showing hyperautofluorescent choroidal vessels in both nasal and temporal, or only the nasal, portions of the fundus using fundus autofluorescence. Methods: Nineteen eyes with hyperautofluorescent vessels in both nasal and temporal portions (group 1) and 17 only the nasal portion (group 2) of the fundus were studied. Choroidal and retinal thicknesses (foveal, and nasal and temporal 3,000 µm from the fovea), axial length, and refraction were compared between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Parapapillary diffuse choroidal atrophy, which involves extreme thinning of parapapillary choroid 42 , is a potential precursor of pathologic myopia 43 . The CT is correlated negatively with the AL in patients with high myopia 29 , 30 and healthy subjects 31 Our results also showed that the CT is correlated negatively with the AL. We can suggest two plausible explanations for the association between the TBUT and CT. First, since increased parasympathetic tone enhances both the CT 27 and the amount of tear secretion from the lacrimal glands 28 , our results suggested that a “factor X”, including the parasympathetic nervous system, might be a common factor upstream in the association between the TBUT (DED) and CT (myopia) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Parapapillary diffuse choroidal atrophy, which involves extreme thinning of parapapillary choroid 42 , is a potential precursor of pathologic myopia 43 . The CT is correlated negatively with the AL in patients with high myopia 29 , 30 and healthy subjects 31 Our results also showed that the CT is correlated negatively with the AL. We can suggest two plausible explanations for the association between the TBUT and CT. First, since increased parasympathetic tone enhances both the CT 27 and the amount of tear secretion from the lacrimal glands 28 , our results suggested that a “factor X”, including the parasympathetic nervous system, might be a common factor upstream in the association between the TBUT (DED) and CT (myopia) (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Choroidal vessels have been visualized as hyperautofluorescent linear lines on short-wavelength FAF in studies in the past. This FAF finding has been typically described in conditions (choroidal sclerosis and high myopia) wherein the RPE and choriocapillaris have undergone thinning and hence led to enhanced visualization of underlying larger choroidal vessels 28,29 . We observed similar findings in one of our subjects wherein diffuse RPE and choriocapillaris atrophy secondary to CSCR lead to clearly visible hyperautofluorescent pachyvessels on FAF (bottom right Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Others, as well as our team, have reported that myopia is associated with subfoveal choroidal thickness which is significantly related to refractive error ( 13 15 ) and axial length ( 13 , 16 ). Choroidal thickness is also reported to fluctuate in response to diurnal variation and changes in visual input ( 17 19 ).…”
Section: Choroidal Thickness and Myopiamentioning
confidence: 70%